PENGEMBANGAN MEDIA KOMIK TANPA TEKS UNTUK MENULIS PERCAKAPAN BAHASA INGGRIS BAGI SISWA KELAS V SD GODWINS SCHOOL SURABAYA - Fenty Rosida (p-ISSN 2356-0576, 2020)
Abstract: Teaching English emphasizeson four language skills.Writing skill is the most difficult aspect of thefourlanguage skills, especially for elementary school students. Characteristics of elementary students require learning media that are expected to facilitate students to understand the material being studied, especially in writing.This study aims to develop comic without text to write English conversations and to find out the feasibility of comic without text as a medium for writing.The type of research used was Research and Development (R&D). The development procedure used was a development procedure from Borg & Gall (2003). Dissemination stepwas not taken due to limited resources and the ability of researchers. Based on the results of the research that has been done, the results obtained, as a whole meet the eligibility criteria after passing the overall validation, namely from material expert has very good and valid qualifications, media experts and assessment of friend have very good and decent qualifications, and from student trials obtained a percentage of 89%. Then it can be concluded that the development of learning media comic without text is very feasible to be used as a medium for learning writing.Keywords: Learning Media, Comic Without Text